Алгоритм успеха: Повести / Аэлита Ассовская - Ассовская Аэлита Сергеевна (Лениздат, 1990)
Экземпляры: ф.2 (1991) / Инвентарный номер: 22295 / Цена: 1.10 / Авт.знак: А90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6